Is living alone associated with mortality among older primary care patients with or without diabetes? - Anna-Kaisa Aro; Merja Karjalainen; Miia Tiihonen; Hannu Kautiainen; Juha Saltevo; Maija Haanpää; Pekka Mäntyselkä (BMC Primary Care)
Abstract Aims The aim of this study was to evaluate the association between living alone and mortality among older patients with and without diabetes. Methods Electronic patient records were used to identify patients at least 65 years of age with a diagnosis of diabetes and two age- and sex-matched controls without diabetes for each patient with diabetes in 2015. The study population in this analysis consisted of 429 patients with diabetes and 650 controls who returned a questionnaire that contained questions about their diseases, symptoms, and functions. The mortality (2015–2019) data were based on the national registry of Statistics Finland. Cumulative mortality was estimated with Kaplan–Meier’s method and compared with the log-rank test. Cox proportional hazards regression was used to estimate the adjusted hazard ratios (HR) and their 95% confidence intervals (CI). Results The median follow-up time was 4.3 years. 208 of the controls (32%) and 156 (36%) of the patients with diabetes lived alone. Of the controls, 8.1% (95% CI 5.9–11.1) of those not living alone and 20.2% (95% CI 15.3–26.3) living alone died. The corresponding numbers for patients with diabetes were 15.1% (95% CI 11.3–19.8) and 28.8% (95% CI 22.4–36.7). Among all patients, living alone was associated with increased mortality (HR = 1.84; 95% Cl 1.30–2.61), whereas the diagnosis of diabetes was not (HR = 1.31; 95% Cl 0.94–1.81). Conclusions The results of this study show that living alone had a significant impact on the mortality of older patients, regardless of whether they had diabetes or not. Diabetes was not clearly associated with the increased mortality among these older home-dwelling patients.